DEVELOPMENT OF CASTICIN-LOADED ETHYL CELLULOSE MICROPARTICLES BY SOLVENT EVAPORATION METHOD WITH SINGLE EMULSION SYSTEM - ROSTINAWATI, TINA; MUHAIMIN, MUHAIMIN; CHAERUNISAA, ANIS YOHANA; HAZRINA, AGHNIA (International Journal of Applied Pharmaceutics, 2023)
Objective: Casticin (Vitexicarpin) has shown immunoregulatory, antitumor, cytotoxicity, anti-inflammatory and analgesic properties. Application of the valuable bioactive compounds can be limited by their unpleasant taste, low bioavailability, volatilization of active compounds, sensitivity to the temperature, oxidation and UV light, as well as in vivo instability. The problem can be solved by coating the Casticin with a microencapsulation technique. The purpose of this research was to formulate the microcapsules of Casticin with solvent evaporation technique using Ethocel 10 cP. Methods: The microencapsulation process of Casticin was done by solvent evaporation technique (O/W: oil in water). The formula of Casticin microcapsules were designed into three formulas (Ethocel 10 cP: 10%, 15% and 20%). Microcapsules of Casticin were characterized for particle size, in terms of surface morphology by scanning electron microscope (SEM), encapsulation efficiency and release test. Results: In this research, the micoparticles containing Casticin has been developed by using ethyl cellulose (Ethocel 10 cP) as the polymer matrix. The results showed that high concentration of polymer (Ethocel 10 cP) used in microencapsulation resulted in better Casticin microcapsules in terms of physical characteristics. Particle size of microcapsules containing Casticin were in the range of 42.51 to 61.47 μm. Encapsulation efficiency (% EE) was categorized as good because the value were ≥ 80% to, which 91.57% to 96.24%. SEM picture of Casticin microcapsules revealed that the surface of microcapsule were a smooth surface and no pores of microcapsule were obtained. When Eudragit E100 used as a polymer, a rough and porous surface of microcapsule were obtained. Conclusion: It can be concluded that microcapsules of Casticin can be prepared by solvent evaporation method with a single emulsion system (O/W) using Ethocel 10 cP as polymer. Characterization of the microcapsules revealed that ethyl cellulose used on this method is applicable to produce microcapsules which stable in physical properties. A higher polymer concentration led to a more viscous solution, which delayed the polymer precipitation and resulted in a less porous polymer matrix with a slower drug release.